Gender, ethnicity and climate change in Mexico: An analysis of vulnerability and resilience based on household surveys - Lykke E. Andersen; Anna Sophia Doyle; Dorte Verner; Manfred Wiebelt (Institute for Advanced Development Studies (INESAD), 2014)
This paper analyzes gender and ethnic differences in vulnerability and resilience to external shocks and stresses in Mexico. Vulnerability and resilience are measured by a combination of the level of household incomes per capita and the degree of diversification of these incomes. Thus, households which have poorly diversified incomes falling below the national poverty line are classified as highly vulnerable, whereas households which have highly diversified incomes above the poverty line are classified as highly resilient. The analysis shows that both gender and ethnicity are almost irrelevant as explanatory factors of vulnerability whereas education levels, dependency ratios and the age of the head of household are very important. Determining the true factors that affect vulnerability is important in order to devise effective policies to reduce vulnerability.
Keywords: D13; I32; O54; 330; livelihood diversification; resilience; vulnerability; external shocks; gender; ethnicity; Mexico